Numerical and Experimental Analysis of Electromagnetic Scattering Characteristics of Wood Beams and Wood Logs Using a UWB Vivaldi Antenna - Mudrik Alaydrus; Desi Ekowati (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2026)
This paper presents a numerical and experimental investigation of the electromagnetic scattering characteristics of wood beams and wood logs using a ultra-wideband (UWB) Vivaldi antenna. Understanding the interaction between electromagnetic waves and wooden materials is important for applications involving nondestructive sensing, vegetation-aware propagation modeling, and microwave material characterization. A UWB Vivaldi antenna was designed, fabricated, and experimentally validated through reflection coefficient and radiation pattern measurements. The scattering behavior of wooden objects was subsequently analyzed using full-wave electromagnetic simulations and controlled measurements employing a two-antenna transmission configuration. Wood beams and wood logs with different geometries and orientations were investigated to evaluate the influence of object shape, rotational angle, and operating frequency on transmission characteristics. The results demonstrate good agreement between simulation and measurement, confirming the validity of the proposed approach. For wood beams, the transmission coefficient exhibits limited angular dependence at lower frequencies but stronger attenuation effects at higher frequencies. In the case of wood logs, larger objects introduce significantly greater transmission loss and stronger orientation-dependent variations compared with smaller logs. These findings indicate that electromagnetic scattering in wood is strongly influenced by geometry, size, and frequency. The proposed study contributes to a deeper understanding of electromagnetic wave interaction with wooden structures and supports future developments in microwave sensing, radar systems, forestry diagnostics, and vegetation-related propagation analysis.